2011
DOI: 10.1002/jso.21897
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of peritumoral and subareolar injection of blue dye alone, for identification of sentinel lymph nodes in patients with early stage breast cancer

Abstract: The use of MB alone is an efficient method for identification of the SLN. The PT injection route yields a higher number of SLNs than the SA route, comparable with the number of SLNs retrieved, when combined tracing agents and multiple injection sites are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The risk of bias assessment of the two RCTs demonstrated that they both possessed adequate sequence generation, calculation of a power analysis, satisfactory randomization, concealed allocation, addressed incomplete data, and were free from selective reporting and other biases ( Table ; Table S6 , supporting information). However, neither study stated whether the clinicians or patients in the trial were blinded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of bias assessment of the two RCTs demonstrated that they both possessed adequate sequence generation, calculation of a power analysis, satisfactory randomization, concealed allocation, addressed incomplete data, and were free from selective reporting and other biases ( Table ; Table S6 , supporting information). However, neither study stated whether the clinicians or patients in the trial were blinded.…”
Section: Resultsmentioning
confidence: 99%
“…These 18 studies underwent full‐text review and one further study was excluded from the systematic review on the basis of the absence of a preoperative diagnosis of invasive or in situ malignancy. Of the 17 studies remaining, another four were excluded from the meta‐analysis because there was no comparison of superficial versus deep injections of radiotracer with or without blue dye. Thus a total of 13 studies met the inclusion criteria for meta‐analysis ( Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, skin, fat and parenchymal necrosis have been reported [ 63 , 64 ]. Among the 18 studies included in present meta-analysis, Brahma reported that two patients experienced skin necrosis around the MBD injection site[ 44 ]; East reported that on patients developed skin and subcutaneous tissue necrosis around the MBD subareolar injection site[ 36 ]; and Kaklamanos reported that 3 patients suffered from skin allergic reaction[ 37 ]. No fat or parenchymal necrosis was reported.…”
Section: Discussionmentioning
confidence: 99%
“…A transverse line marking the SLNB incision was drawn in the axilla about 2 cm below the axillary hair-bearing area. After induction of general anesthesia, 2 mL of methylene blue dye was injected in the subareolar area 16,22 and the injection site was massaged for 5 min. Then, the subcutaneous tissue beneath the marked line was cut open through the transverse skin incision of the modified radical mastectomy.…”
Section: Methodsmentioning
confidence: 99%